APLIKASI METODE QUALITY FUNCTION DEPLOYMENT DALAM PENGEMBANGAN DESAIN ALAT BANTU MAKAN BAGI PENDERITA TUNA DAKSA - Emmy Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2017)
Humans who has a perfect physical can easily perform daily activities, one of which is eating. For upper limb disabled people, eating activity is very difficult. This research is for create and develop of assistive tool for eat that can meet the needs of users (upper limb disabled people), technical requirements, convenience of usability, ergonomicÂ assistive tool for eat . The method used to create and develop ofÂ assistive tool for eat (Adjusted Spoon V2) is the Quality Function Deployment (QFD). Based on House of Quality (HOQ) matrix results, the first technical requirement is the motion mechanisms (priority 52.44%), second is spring (38.64% priority), third is digitalization (priority 8.92%). The results of this research are Adjusted Spoon V2 prototype that developed to be able to meet the needs of upper limb disabled people in eating activities that include spoon movementÂ flexibility, stick movement flexibility and treadle flexibility, making it easier for them to operate it.